Learners' Mental Models of Metallic bonding: A Cross-Age Study - Coll, R.; Treagust, David (Wiley Interscience, 2003)
Mental models of metallic bonding held by learners from three academic levels, secondary school (year 12), undergraduate and postgraduate, were probed using semistructured interviews including the use of Interviews-About-Events focus cards depicting metallic properties and cards containing depictions of models from curriculum material. The learners in this study hold realist views about the bonding and structure for metallic substances and prefer the sea of electrons model. However, the undergraduate and postgraduate learners commonly utilized concepts from other models, such as the molecular orbital theory, to supplement their descriptions of their mental models. In addition, they were more critical of depicted models and held views of the continuous nature of metallic lattices that were more in accord with the scientific view. Few of the learners were able to describe the bonding in alloys, and although learners across all three academic levels offered reasonable explanations for the conductivity of metals, they were unable to explain malleability. It is recommended that it may be prudent to postpone the teaching of highly abstract mental models until later in an undergraduate degree program, since exposure to complex and abstract models is more appropriate for learners who wish to continue their studies in chemistry.